PENGARUH KARAKTER KEWIRAUSAHAAN TERHADAP KEMAMPUAN USAHA DI SEKTOR HORTIKULTURA PROVINSI JAWA BARAT - Yuliana Samantha; Ronnie S. Natawidjaja; Tuhpawana P. Sendjaja (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
Most of Indonesia's population depend on agriculture. Agriculture is the basis for growth in the countryside. Horticultural company is a company form of business or legal entity that is engaged in the cultivation or breeding and marketing of vegetables, fruit, and ornamental plants. The research design used quantitative descriptive technique and take a case in Horticultural Company incorporated in the province of West Java. Informants research is the founder of 35 businesses horticultural businesses. Respondents were selected by simple random samplingmethod Solvin. Data were analyzed with path analysis, the business environment variables, entrepreneurial character, the ability of businesses and business improvement. Character of business founders age at age less than 54 years, including age. Average of the last education strata 1 (undergraduate). A conducive business environment and the higher the entrepreneurial character can give the effect of an increase in the ability of the business. Theseeffects are direct and indirect, of the path of the business environment 78.3%, 19.2% and entrepreneurial character. The effects of both variables 83.7% with 4% residual business capabilities and 16.3% influenced by other variables that are not covered.